Role of management control systems in crafting realized strategies - Naranjo-Gil, David (Journal of Business Economics and Management, 2016)
The distinction between deliberate and emergent strategy implementation is rarely acknowledged in management control literature, which has promoted a passive view of control systems tailored explicitly to support the strategic planning. This paper analyzes how management control systems facilitate organizations to realize their intended strategies. Hypotheses are tested using survey data from CEOs of Spanish hospitals. Partial least squares is used as a statistical technique to test the integral causal path model. Results show that boundary and diagnostic control systems have primarily a positive impact on the realization of deliberate strategies, whereas belief and interactive control systems positively affect emergent strategies. This study tries to clarify the fragmented results of the literature by analyzing the effect of the design (passive role) and the use (active role) of management control systems on both deliberate and emergent strategies. A practical implication of this paper is that managers should focus on both the design and the use of management control systems to implement strategies successfully. This study is among the first to provide empirical evidence on how different levers of control complement each other in crafting realized strategies.